2022
DOI: 10.1101/2022.08.04.502823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fundamental metabolic strategies of heterotrophic bacteria

Abstract: Through their metabolism, heterotrophic microbes drive carbon cycling in many environments. These microbes consume (and produce) hundreds to thousands of different metabolic substrates, begging the question of what level of description is required to understand the metabolic processes structuring their communities: do we need to account for the detailed metabolic capabilities of each organism, or can these capabilities be understood in terms of a few well-conserved carbon utilization strategies that could be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…Because these traits are quantitatively similar in phylogenetically related taxa, related species can fulfill equivalent functional roles leading to communities with similar coarse-grain phylogenetic compositions despite differences at the species level (Martiny et al 2015; Aguirre de Cárcer 2019; Estrela, Vila, et al 2022). Additionally, recent studies involving high-throughput measurements of microbial growth phenotypes and pairwise inter-specific interactions in different environments have shown that different environments can sometimes be ’coarse- grained’ and grouped together based on the chemical class of substrate present (Tong et al 2020; Kehe et al 2021; Gralka, Pollak, and Cordero 2022). These two observations suggest that similar initial metabolic environments may lead to quantitative similarities in metabolic traits, which we reasoned would lead to selection for quantitatively similar communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because these traits are quantitatively similar in phylogenetically related taxa, related species can fulfill equivalent functional roles leading to communities with similar coarse-grain phylogenetic compositions despite differences at the species level (Martiny et al 2015; Aguirre de Cárcer 2019; Estrela, Vila, et al 2022). Additionally, recent studies involving high-throughput measurements of microbial growth phenotypes and pairwise inter-specific interactions in different environments have shown that different environments can sometimes be ’coarse- grained’ and grouped together based on the chemical class of substrate present (Tong et al 2020; Kehe et al 2021; Gralka, Pollak, and Cordero 2022). These two observations suggest that similar initial metabolic environments may lead to quantitative similarities in metabolic traits, which we reasoned would lead to selection for quantitatively similar communities.…”
Section: Introductionmentioning
confidence: 99%
“…S4B). Recent studies have classified carbon sources based on whether they enter metabolism via glycolysis (glycolytic) or the TCA cycle (gluconeogenic) (Gralka et al 2022, Borer et al 2022). When we classify our 19 carbon sources along this binary, we find that all eight carbon sources on which E+ grew significantly faster than P+ were glycolytic, whereas all nine carbon sources on which P+ grew significantly faster than E+ were gluconeogenic (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The questions about the ecology and evolution of metabolic hierarchies have received renewed a ention in recent years (Bajic and Sanchez 2020;Okano et al 2021), as part of the ongoing effort to understand the drivers of microbial community assembly and coexistence (Chang et al 2022;Estrela et al 2022;Gralka et al 2022). Recent theoretical work (Posfai et al 2017;Goyal et al 2018;Pacciani-Mori et al 2020;Wang et al 2021;Bloxham et al 2023) and experiments with model communities (Pacciani-Mori et al 2020;Bloxham et al 2022) have shown that differences in metabolic hierarchies can impact ecology, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, evolutionary effects cannot be decoupled from ecological ones, as both can occur at contemporary timescales [68, 69] and microbial communities often exhibit a very large fine-scale diversity in the form of multiple co-occurring phenotypes [70]. Importantly, such a diversity is nowadays accessible to experiments owing to technological advances in determining single-cell traits [31, 71, 72] and metabolic functions [7376]. All this calls for the development of novel eco-evolutionary frameworks —extending existing ones— to analyze complex microbial communities, with individuals distributed in phenotypic space and evolving on ecological time scales.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, such a diversity is nowadays accessible to experiments owing to technological advances in determining single-cell traits [31,71,72] and metabolic functions [73][74][75][76]. All this calls for the development of novel ecoevolutionary frameworks -extending existing ones-to analyze complex microbial communities, with individuals distributed in phenotypic space and evolving on ecological time scales.…”
Section: Introductionmentioning
confidence: 99%